The effects of formative tests and students’ thinking styles on English study - Binfas, Maman A. Majid; Dewi Awaliah,; Hasmawati,; Ernawati, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2021)
English has a position as a foreign language in Indonesia and universal language in the world. It means that, English is very important as a tool of communication for most countries in the world. Therefore, Indonesian government put English in the curriculum 2006 as one of the subjects which has to be taught in Senior High School. On the other hand, many students have difficulties in studying English because English is not their first language. The students need given a formative test in studying English. The objective of this study is to analyze and to find out the influences of formative test and students’ thinking style in studying English. The thinking style used in the study is lateral and vertical thinking styles with formative essay and multiple-choice tests. This study uses quantitative method. The design of this study is experimental design. The result of calculation showed that in the significance degree of 5%, the variant analyzes with Turkey-test to saw which one the groups is more excellent than others. The result showed that: first, there was a significant difference between students who were given formative essay and multiple-choice tests (Fh = 4,189 > 4,043 = Ft ); second, there was a significant difference between students who had lateral and vertical thinking styles (Fh = 4,238 > 4,043 = Ft ); third, there was correlation between formative test and students’ thinking style toward students’ ability in studying English (Fh = 25,237 > 4,043 = Ft ). Based on the criteria of the test showed that students who have been given formative essay test with lateral thinking style was effective than students who have been given multiple-choice test with vertical thinking style in studying English at the classroom.